Global polio switch and introduction of inactivated polio vaccine in routine immunization: are medical interns aware? - Kadarkar, Kalpak S.; Dhok, Rajeshree S.; Doibale, Mohan K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Health care providers play important roles in parent/caregiver acceptance. They need to provide strong support for BOPV, IPV (Inactivated polio vaccine) and multiple vaccine injections. They must be prepared to answer parents or caregiver questions. Aim of this study to assess knowledge, awareness and perception of medical interns regarding OPV switch, IPV introduction, Polio eradication, factors demanding switch and multiple vaccine delivery at single visit. Methods: A cross-sectional study was carried out among interns medical college in February 2016. They were requested to complete questionnaire regarding polio eradication, OPV switch, IPV introduction, need of switch and multiple vaccine delivery. Results: 90.63% of interns had an idea about planned introduction of IPV vaccine in routine immunization. 2/3rd of interns had an idea about switch from TOPV to BOPV. Only 43.75% interns answered that direction of switch from TOPV to BOPV. Only 26.56% interns correctly said that there is need of multiple vaccines at single visit but 67.19% did not feel any need of that. Study highlights low level of awareness regarding switch, IPV introduction in RI and also many misconception regarding multiple vaccine delivery system. Conclusions: All these gaps are to be managed quickly through proper and timely training regarding recent advances in public health, CMEs, interactive sessions and forum where all doubts and aspects of IPV, BOPV and multiple vaccines can be clarified.